Microvesicles in hepatic and peripheral vein can predict nonresponse to corticosteroid therapy in severe alcoholic hepatitis. Issue 8 (20th February 2018) - Sukriti, S.; Maras, J. S.; Bihari, C.; Das, S.; Vyas, A. K.; Sharma, S.; Hussain, S.; Shasthry, S.; Choudhary, A.; Premkumar, M.; Kumar, D.; Kumar, G.; et al.
Summary: Background: Severe alcoholic hepatitis patients have high mortality and limited response to corticosteroids. Microvesicles reflect cellular stress and disease conditions. Aims: To investigate whether microvesicles are associated with severity, response to steroid therapy and inflammation in severe alcoholic hepatitis. Methods: Microvesicles originating from different cells were studied pre‐therapy in 101 patients; (71 responder to corticosteroid therapy and 30 nonresponders) and 20 healthy controls. Microvesicles and cells were determined in peripheral and hepatic vein samples using flow cytometry and correlated with outcomes. Inflammatory signalling pathways and functional alterations of immune cells after stimulation with microvesicles were also investigated. Results: Microvesicles mean levels were higher in nonresponders for T cells (CD3 + CD4 + ; 10.1 MV/μL vs 5.4; P = 0.06), macrophages (CD68 + CD11b + ; 136.5 vs 121.9 MV/μL; P = 0.01), haematopoietic stem‐cells (CD45 + CD34 + ; 116.8 vs 13.4 MV/μL; P = 0.0001) and hepatocytes (ASGPR + ; 470 vs 361 MV/μL; P = 0.01); the latter two predicting steroid nonresponse in 94% patients at baseline in peripheral plasma. Microvesicle levels correlated with histological and liver disease severity indices. Whereas, in non‐responders hepatic vein CD34+ cells were lower ( P = 0.02), the CD34+ microvesicles there from were higher ( P = 0.04), thus suggesting impaired regeneration. Also, microvesicles of 0.2‐0.4 μm size were higher in nonresponders ( P < 0.03) at baseline. Microvesicles from patients trigger more ( P = 0.04) ROS generation, TNF‐α production ( P = 0.04) and up‐regulate pro‐inflammatory cytokine related genes in neutrophils in vitro. Conclusions: Pre‐therapy peripheral plasma levels of CD34 + and ASGPR + microvesicles are reliable non‐invasive markers of steroid nonresponse and mortality in patients with severe alcoholic hepatitis.